2017
DOI: 10.1002/ima.22262
|View full text |Cite
|
Sign up to set email alerts
|

Focused ultrasound brain stimulation to anesthetized rats induces long‐term changes in somatosensory evoked potentials

Abstract: Low-intensity transcranial focused ultrasound (FUS) has emerged as a non-invasive brain stimulation modality that can reach deep brain areas with high spatial specificity. Previous studies have identified transient effects of FUS on the brain excitability and accompanying physiological responses. Yet the presence of long-lasting effects of FUS, which extend on the order of half an hour or more, has not been probed. We transcranially applied FUS to the somatosensory areas of the anesthetized rats for 10 min at … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
38
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
4
4
1

Relationship

1
8

Authors

Journals

citations
Cited by 42 publications
(39 citation statements)
references
References 32 publications
1
38
0
Order By: Relevance
“…A small (16 mm in diameter, 12 mm in height) and light (~ 6 g in weight) FUS transducer was built in-house (Fig. 1 a) [ 44 ]. A disc-shape zirconate titanate (PbZr x Ti (1−x) O 3 ; PZT) ceramic (American Piezo Ceramics, Mackeyville, PA) was used and fitted (air-backed) inside of a custom-built plastic housing.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…A small (16 mm in diameter, 12 mm in height) and light (~ 6 g in weight) FUS transducer was built in-house (Fig. 1 a) [ 44 ]. A disc-shape zirconate titanate (PbZr x Ti (1−x) O 3 ; PZT) ceramic (American Piezo Ceramics, Mackeyville, PA) was used and fitted (air-backed) inside of a custom-built plastic housing.…”
Section: Methodsmentioning
confidence: 99%
“…To enable the experimentation in freely-moving small animals, one critical technical element is to make the transducer wearable. Accordingly, we developed a miniaturized, light-weight FUS transducer that can be worn (and detachable) by Sprague–Dawley rats (anesthetized) and demonstrated that FUS can be delivered to their primary somatosensory areas, with possibility for inducing long-term neuromodulatory effects [ 44 ]. A 3D-printed applicator that is designed to adjust the position of the transducer was attached to a pedestal, which was implanted onto the rat skull.…”
Section: Introductionmentioning
confidence: 99%
“…One step further than studying ultrasound effects on single cortical neuronal activities, we investigate potential sustained therapeutic effects of acoustic energy on inter-neuronal synaptic connectivity at deep brain. tFUS targeting the deep brain were demonstrated recently (Dallapiazza et al, 2018;, and non-transient neuromodulatory effects were also observed in anesthetized rat Yoo et al, 2017) and monkey models. These are early evidences of ultrasound-induced neuroplasticity, a concept which we further explored in the well characterized system of hippocampal long-term potentiation (LTP) and depression (LTD) in rats.…”
Section: Introductionmentioning
confidence: 92%
“…A total of 156 articles were subjected to full-text review, of which 121 articles were removed for the following reasons: review or commentary ( n = 52), study regarding the application of ultrasound in neurosurgery ( n = 7), technique papers regarding the design of ultrasound system, stimulation protocol, parameter optimization and properties improvement ( n = 39), computational modeling or simulation study ( n = 4), ultrasonic stimulation targeting peripheral or cranial nerves rather than cortical and subcortical structures ( n = 4), study with surrogate biomarkers as outcomes exclusively ( n = 14), study regarding seizure control ( n = 1) and study using mixed ultrasound magnetic stimulation ( n = 1). Ultimately 35 studies (Tufail et al, 2010; Yoo et al, 2011a,b, 2018; Deffieux et al, 2013; Hameroff et al, 2013; Kim et al, 2013, 2014a,b, 2015; Legon et al, 2014, 2018a,b; Chu et al, 2015; Guo et al, 2015, 2018; Lee et al, 2015, 2016a,b,c; Ai et al, 2016, 2018; Monti et al, 2016; Yu et al, 2016; Wattiez et al, 2017; Dallapiazza et al, 2018; Daniels et al, 2018; Gibson et al, 2018; Sato et al, 2018; Xie et al, 2018; Yang et al, 2018; Zhang et al, 2018; Li et al, 2019; Sharabi et al, 2019) were selected for inclusion in this review, including 24 animal and 11 human studies.…”
Section: Resultsmentioning
confidence: 99%